Determination of Active Pharmaceutical Substances Dissolution Rate by Laser Light Diffraction Method - E. V. Uspenskaya; I. V. Kazymova; T. V. Pleteneva; T. E. Elizarova; A. V. Syroeshkin (Разработка и регистрация лекарственных средств)
Introduction. The strategy of quality control of drugs provides for compliance with the requirements of regulatory documentation methods and critical quality indicators that determine its effectiveness. Special attention should be paid to the properties of the initial pharmaceutical substance (lipophilicity logP, area of the topological polar surface of TPSA, particle size, polymorphism), which determine the solubility and dissolution rate of the active pharmaceutical substance (APS) in terms of their impact on the bioavailability of the finished drug in vivo [1–3]. Since the assessment of pharmacopoeia solubility of APS is reduced to a visual procedure and the use of approximate terms, we have developed an original method for determining the dissolution rate of substances using the laws of chemical kinetics. Validation of the analytical method is carried out at introduction of the new method, and also at change of conditions of analysis of medicines carried out during the life cycle (product lifecycle) of a pharmaceutical product and its manufacturing process [4]. The proposed technique for laser determination of the dissolution rate in water of a medicinal substance of fluoroquinolone group has been tested; elements have been included in validation studies: repeatability, precision, linearity and range.Aim. Development of the method for determining the dissolution rate of active pharmaceutical substances by laser light diffraction with validation elements.Materials and methods. Determination of the dissolution rate of moxifloxacin hydrochloride was carried out in water for laboratory analysis of purity level 1 (ultra-pure water) obtained on the Milli-Q® Integral, the quality of which corresponds to ISO 3696:1987. To achieve this goal, a pharmacopoeia method of research was used – low-angle scattering of laser light (laser diffraction method); instrument equipment – laser dispersion meter Malvern 3600 EC.Results and discussion. An additional analytical method for determination of API dissolution rate by laser light diffraction method was developed. Validation studies on parameters: precision (repeatability, intra-laboratory/intermediate), linearity, analytical region. Precision was estimated based on the results of 18 measurements, the coefficient of variation was 8 %, the relative error of average 4 %. Linearity was determined (correlation coefficient R = 0.992). The range of application of the analytical technique depends on its purpose, is determined in the linearity analysis and ranges from 5 · 10-3 g/ml to 5 · 10-2 g/ml.Conclusion. The proposed methodology can be used as an independent test of the properties of pharmaceutical substances both at the stage of their development and preclinical studies, and in the process of quality control in addition to the existing pharmacopoeia test to assess the solubility of pharmaceutical substances, expressed in terms of conditional.